The effect of job referrals on labor market outcomes in Brazil - Christopher J. O'Leary; Túlio Cravo; Ana C. Sierra; Leandro Justino (Inter-American Development Bank (IDB), 2019)
This paper is the first to use program administrative data from Brazil's National Employment System (SINE) to assess the impact of SINE job interview referrals on labor market outcomes. Data for a five-year period (2012-2016) are used to evaluate the impact of SINE on employment probability, wage rates, time until reemployment, and job tenure. Difference-in-differences estimates suggest that a SINE job interview referral increases the probability of finding a job within three months of the referral and reduces the number of months to find reemployment, the average job tenure of the next job, and the reemployment wage. Subgroup analysis suggests that compared to more educated workers, SINE is more effective in helping less educated workers by increasing their probability of finding a job and reducing time until reemployment. Finally, the evidence suggests that online labor exchange is less effective than the service provided in person at SINE offices.
Keywords: J18; J23; J68; 330; employment agencies; labor market policy; employment services; labor exchange; job matching; job interview referrals; difference-in-differences